2020
DOI: 10.1371/journal.pntd.0008358
|View full text |Cite
|
Sign up to set email alerts
|

T. brucei infections abrogate diverse plasma cell-mediated effector B cell responses, independently of their specificity, affinity and host genetic background

Abstract: Antibody-mediated parasite killing is considered the most effective host immune response against extracellular trypanosome parasites. However, due to host-parasite co-evolution pressure, these parasites have "learned" how to hijack the host immune system via the development of immune evasion strategies. Hereby they prevent elimination and promote transmission. In the past, our group has shown that African trypanosome parasites are able to "shut down" the host B cell compartment, via the abolishment of the home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Interestingly, DIZE treatment restored the clinical signs of the disease, with authors attributing the reversal to the restoration of specific autoimmune antibody levels. However, a recent study by the same group showed that DIZE treatment did not restore the thymo-dependent and independent humoral response or the vaccine-induced memory response (antibody levels) in malaria-vaccinated C57BL/6 mice following T. brucei infection [ 133 ]. Moreover, the authors proposed that vaccine memory was partially destroyed or the accessibility to those memories was prohibited by infection, further highlighting the need for malaria vaccine trials in areas where trypanosomiasis is prevalent.…”
Section: Diarylamidines Serine Proteasesmentioning
confidence: 99%
“…Interestingly, DIZE treatment restored the clinical signs of the disease, with authors attributing the reversal to the restoration of specific autoimmune antibody levels. However, a recent study by the same group showed that DIZE treatment did not restore the thymo-dependent and independent humoral response or the vaccine-induced memory response (antibody levels) in malaria-vaccinated C57BL/6 mice following T. brucei infection [ 133 ]. Moreover, the authors proposed that vaccine memory was partially destroyed or the accessibility to those memories was prohibited by infection, further highlighting the need for malaria vaccine trials in areas where trypanosomiasis is prevalent.…”
Section: Diarylamidines Serine Proteasesmentioning
confidence: 99%